Woman as Colonized Subject: Ahmed Ali Versus Shahnawaz - Ahmed, Zia; Hussain, Zahoor; Ausaf, Sana (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the difference of representation of women by Ali and Shahnawaz and attempts to find if there was a deliberate exclusion of women in the fiction of Ali in comparison to that of Shahnawaz. Shahnawaz’ portrayal of women in her novel The Heart Divided reflects women’s active participation in the socio-political process under the British rule in India while at the same time Ali’s portrayal of women in his novel Twilight in Delhi reflects an exclusion of women, especially from the political process. This evident difference problematizes the issue of representation of women by the fiction writers and initiates the debate whether it was a deliberate exclusion of women in one case and the willful inclusion of women in another. Portrayal of Mehruin Ali’s Novel Twilight in Delhi and that of Zohra in Shahnawaz’s novel The Heart Divided has been analyzed to find the most probable answer to this question with reference to the socio-political situation in India as a British colony.